Epigenetic responses in Borrelia-infected Ixodes scapularis ticks: Over-expression of euchromatic histone lysine methyltransferase 2 and no change in DNA methylation - Grace Hadley MacIntosh; Alexandra C. Nuyens; Jessica L. Vickery; Anne Berthold; Vett K. Lloyd (PLoS ONE, 2025)
Borrelia burgdorferi, a tick-vectored spirochete bacteria best known for causing Lyme disease, has been found to induce physiological and behavioural changes in its tick vector that can increase tick fitness and its ability to transmit the bacteria. The mechanism by which this bacterium modulates these changes remains unknown. Epigenetics plays a central role in transducing external and internal microbiome environmental influences to the organism, so we investigated DNA methylation and the expression of a key histone modification enzyme in Borrelia-infected and uninfected Ixodes scapularis ticks. DNA methylation of the pericentromeric tandem repeats family, Ixodes scapularis Repeats (ISR), were assessed by methylated-DNA immunoprecipitation (MeDIP) followed by qPCR of the ISR regions. DNA methylation of the ISR sequences was found. The different repeats had different levels of DNA methylation, however, these levels were not significantly affected by the presence or absence of B. burgdorferi. The epigenetic regulator euchromatic histone lysine methyltransferase 2 (EHMT2) is recognized as having a key role in modulating the organismal stress response to infections. To assess EHMT2 transcription in Borrelia-infected and uninfected ticks, real-time reverse transcriptase PCR was performed. Uninfected ticks had over 800X lower EHMT2 expression than infected ticks. This study is among the first to identify a gene that may be involved in producing epigenetic differences in ticks depending on infection status and lays the groundwork for future epigenetic studies of I. scapularis in response to B. burgdorferi as well as other pathogens that these ticks transmit.